SIMULATION OF STAR FORMATIONS IN COSMOLOGICALVOLUME (240 Mpc/h)3 - Rasheed, Mariwan A; Ameen, Mudaffer M (Al-Nahrain Journal of Science, 2018)
In this paper the Lambda Cold Dark Matter (ΛCDM) model was used for studying star formation inside a box of size (240Mpc/h)3 by simulating eight million dark matter particles and eight million gas particles together with cosmological density Ω=0.25, dark energy density ΩΛ=0.75, baryon density Ωb=0.04, fluctuation amplitude σ8=0.9 and Hubble constantH0=100h kms-1Mpc-1 . The gadget-2 code was used for simulating the particles from early Universe, z=30 (450 million years) to z=0 (13.4 billion years). In the box the structures formation were shown including galaxy clusters, voids and filaments which observed clearly at low redshift, z=0. In the temperature-density planes, the thermal processes of cooled gas show the density and temperature values which were different at each redshift, and the gas cooled in the box at nearly 104K caused star formations at certain redshifts. It was also found that stars were formed from z=7.3 which increased with decreasing redshifts. In addition, the total number of star formed in the box was 226217 stars.Sixteen processors of high performance supercomputer of Nottingham University-England were used in the simulation.